Review of the genus Chilotrogus Reitter (Coleoptera: Scarabaeidae: Melolonthinae: Rhizotrogini) in Iran with description of two new species - Miessen, Geoffrey; Uliana, Marco; Keith, Denis (Zootaxa, 2020)
The scarcely known species of Chilotrogus Reitter, 1905 from Iran are revised based on abundant and mostly unpublished material, Chilotrogus matejiceki Miessen, Uliana & Keith, new species and Ch. schoolmeestersi Miessen, Uliana & Keith, new species are described. The type of Chilotrogus panotrogoides Reitter, 1905 is studied and correctly labelled. An identification key is given, as well as an extensive iconography and a distribution map of Iranian species.